2011
DOI: 10.1097/brs.0b013e3181f5cb87
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cervical Spine Biomechanics After Fixed- and Mobile-Core Artificial Disc Replacement

Abstract: The results of our study presented an increase in ROM, facet joint force, and ligament tension at the ADR segments. The mobile-core model showed a higher increase in segmental motion, facet force, and ligament tension, but lower stress on the PE core than the fixed-core model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(84 citation statements)
references
References 0 publications
5
79
0
Order By: Relevance
“…Modest increases (2-15 %) were observed at the Prodisc-C treated level in a finite element study [28]. An apparent increase of facet joint force and ligament tension was also reported at the operative segments [8]. Unlike the fusion condition, the hyper-mobility of the operative site was reversely compensated by a reduced ROM at the adjacent site.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Modest increases (2-15 %) were observed at the Prodisc-C treated level in a finite element study [28]. An apparent increase of facet joint force and ligament tension was also reported at the operative segments [8]. Unlike the fusion condition, the hyper-mobility of the operative site was reversely compensated by a reduced ROM at the adjacent site.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of these artificial discs adopt polymer-on-metal or metal-on-metal design to form a sliding articulation. Despite that these artificial discs have exhibited satisfactory clinical performance, biomechanical studies have shown that the sliding articulation may not well control the motion that will induce hyper-mobility at the operative segment [6][7][8], and the ligament tension was increased in this situation [8]. The wear debris, which was associated with chronic inflammation, was an inevitable situation caused by the sliding articulation design [9].…”
Section: Introductionmentioning
confidence: 99%
“…The intervertebral disc ( Figure 2B) between 4 vertebrae was partitioned into the annulus fibrosus and the nucleus pulposus. The 5 volume of the annulus, which had a five-layered ground substance surrounded by 6 six-layered annulus fibers was about 60% of the total volume of the intervertebral disc 7 [2,26]. Six layers of netlike annulus fibers were positioned between 15° and 45°, 8 against the horizontal plane.…”
mentioning
confidence: 99%
“…Then, a model consisted of vertebral bodies and 11 intervertebral discs was constructed ( Figure 2C). Table 1 [2,20,21,26,[28][29][30]. C3D4 is the tetrahedral solid element with 19 four nodes, C3D8 is the hexahedral solid element with eight nodes, C3D10 is the 20 decahedral with ten nodes, T3D2 is the truss element with two nodes in the ABAQUS 21 software, and the total numbers of nodes and elements are 377,877 and 330,648.…”
mentioning
confidence: 99%
See 1 more Smart Citation